Corrigendum: Secretoneurin levels are higher in dilated cardiomyopathy than in ischaemic cardiomyopathy: preliminary results - Plášek, Jiří; Dodulík, Jozef; Lazárová, Marie; Stejskal, David; Švagera, Zdeněk; Chobolová, Nela; Šulc, Patrik; Evin, Lukáš; Purová, Dana; Václavík, Jan (Frontiers in cardiovascular medicine, 2024)
[This corrects the article DOI: 10.3389/fcvm.2023.1297900.].
Keywords: heart failure; ischaemic cardiomyopathy; dilated cardiomyopathy; secretoneurin; CaMKII